The relevance and social significance of the research of language aggression - Pap, Kinga (MEDIATON OF HUNGARIAN LANGUAGE CULTURE, 2021)
In our research we have approached the phenomenon of language aggression characteristic of the language usage of secondary school students based on their social interactions, the necessity of communication, emphasizing that lanuage aggression is not part of the language but of language usage, so we have used the methods of pragmatics and sociolinguistics to reveal that. We have defined the notion of language aggression, then, based on the empirical data, we have systematized this heterogeneous language usage phenomenon according to functional and formal points of view, with the help of which we could grasp all types of language aggression caracteristic of the language usage of the secondary school age group.